2015
DOI: 10.3311/ppch.7571
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Immersed Herbs on the Oxidative Stability of Edible Oils

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…An addition of 0.005% of lycopene improved walnut oil quality and extended walnut shelf life up to 16 months (Xie et al, 2018). The immersion of herbs (sage and oregano; 3%, 5%, and 7% (w/w) herb/oil; 30 • C for 10 days) increased the oxidative stability of the investigated oils, and particularly oils rich in polyunsaturated fatty acids (Somogyi et al, 2015). When sage, thyme and basil (under different forms: aerial plant intact or part cut into pieces, or leaves only) were added to walnut oil, an increase of the antioxidant activity of walnut oil was mainly observed with sage addition (Laskos et al, 2021).…”
Section: Walnut Oil Stabilitymentioning
confidence: 96%
“…An addition of 0.005% of lycopene improved walnut oil quality and extended walnut shelf life up to 16 months (Xie et al, 2018). The immersion of herbs (sage and oregano; 3%, 5%, and 7% (w/w) herb/oil; 30 • C for 10 days) increased the oxidative stability of the investigated oils, and particularly oils rich in polyunsaturated fatty acids (Somogyi et al, 2015). When sage, thyme and basil (under different forms: aerial plant intact or part cut into pieces, or leaves only) were added to walnut oil, an increase of the antioxidant activity of walnut oil was mainly observed with sage addition (Laskos et al, 2021).…”
Section: Walnut Oil Stabilitymentioning
confidence: 96%
“…The antioxidant capacity of ferric ion reduction in C. longa L. leaves was 217.99 µMol of FeSO 4 .100 g -1 . Somogyi et al (2015) found the following FRAP values for 7% w/w concentration of herbs immersed in vegetable oils: 500, 580, and 600 µMol of FeSO 4 .100 g -1 for dried leaves of sage (Salvia officinalis L., Labiatae) and 300, 310, and 380 µMol of FeSO 4 .100 g -1 for dried leaves of oregano (Origanum vulgare L., Lamiaceae). These values were higher than those found in this study.…”
Section: Peroxide Index (Pi)mentioning
confidence: 98%
“…The GC-FID or GC-MS instruments are suitable for the chromatographic separation and detection of volatile compounds such as ketone bodies [26], alcohol derivatives [27] or FAME species [28,29]. The chromatographic separation of cis and trans (FAME) needs the application of special stationary phases such as propyl-nitrile-polysiloxane [27,30].…”
Section: Introductionmentioning
confidence: 99%